A new feeding group within larval Drusinae (Trichoptera: Limnephilidae): the Drusus alpinus Group sensu Schmid, 1956, including larval descriptions of Drusus franzi Schmid, 1956, and Drusus alpinus (Meyer-Dür, 1875) - Graf, W.; Waringer, J.; Pauls, S. U. (Zootaxa, 2009)
This paper presents a description of the hitherto unknown larvae of Drusus franzi Schmid, 1956, and Drusus alpinus (Meyer-Dür, 1875). Information on the morphological and genetic identification of both species is given, and the most important diagnostic features are illustrated. Their systematic position within the genus Drusus is affirmed and zoogeographical and ecological notes are added.